Solitary Sinonasal Neurofibroma in an Elderly Male: A Rare Presentation and Surgical Management - Jessica Filbertine; I Gde Ardika Nuaba; I Ketut Suanda; Ida Ayu Alit Widiantari; I Wayan Lolik Lesmana (Open Access Indonesian Journal of Medical Reviews, 2025)
Solitary sinonasal neurofibromas are rare peripheral nerve sheath tumors whose diagnosis is frequently confounded by non-specific symptoms and radiological features that mimic common inflammatory conditions. In the elderly, a unilateral sinonasal mass necessitates a high index of suspicion for neoplasia, yet diagnostic pitfalls remain a significant clinical challenge. A 65-year-old male with no stigmata of neurofibromatosis type 1 presented with a three-year history of progressively worsening unilateral nasal obstruction. Endoscopy revealed a large, pale, firm, non-friable mass. Computed tomography (CT) demonstrated an extensive, non-enhancing soft tissue mass originating in the left maxillary sinus, causing significant expansile bone remodeling and extending into multiple adjacent sinuses. The initial radiological impression was extensive sinonasal polyposis. However, an incisional biopsy followed by a comprehensive morphological analysis confirmed the diagnosis of a benign spindle cell tumor consistent with neurofibroma. The patient underwent complete tumor excision via a left lateral rhinotomy. The postoperative course was uneventful, with no recurrence at 12-month follow-up. In conclusion, this case underscores the critical importance of a thorough diagnostic workup for unilateral sinonasal masses in the elderly, where radiological findings can be misleading. Histopathological analysis is indispensable for the definitive diagnosis of spindle cell tumors in this location. For massive, maxillary-based neurofibromas with extensive lateral and anterior involvement, the lateral rhinotomy remains a vital and superior surgical approach, providing the necessary exposure to uphold the fundamental principle of complete oncologic resection and maximize the probability of a curative outcome.